2021
DOI: 10.1002/cssc.202100262
|View full text |Cite
|
Sign up to set email alerts
|

Fast Addition of s‐Block Organometallic Reagents to CO2‐Derived Cyclic Carbonates at Room Temperature, Under Air, and in 2‐Methyltetrahydrofuran

Abstract: In memory of Prof. Victor Snieckus, a leading authority in organolithium chemistry and directed ortho-metalation reactions.Fast addition of highly polar organometallic reagents (RMgX/ RLi) to cyclic carbonates (derived from CO 2 as a sustainable C1 synthon) has been studied in 2-methyltetrahydrofuran as a green reaction medium or in the absence of external volatile organic solvents, at room temperature, and in the presence of air/moisture. These reaction conditions are generally forbidden with these highly rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 86 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…The catalytic cycloaddition of CO 2 to epoxides is a valuable non-reductive approach to pursue the highly sought-after CO 2 capture and fixation into useful commodity chemicals. The produced cyclic organic carbonates serve as solvents, as monomers for the preparation of isocyanate-free polyurethanes, and as powerful intermediates for the synthesis of manifold chemicals. It is clear that for cyclic carbonates to serve as commodity chemicals, inexpensive, efficient, and recoverable catalytic systems that are active under mild conditions of temperature and pressure are required …”
Section: Introductionmentioning
confidence: 99%
“…The catalytic cycloaddition of CO 2 to epoxides is a valuable non-reductive approach to pursue the highly sought-after CO 2 capture and fixation into useful commodity chemicals. The produced cyclic organic carbonates serve as solvents, as monomers for the preparation of isocyanate-free polyurethanes, and as powerful intermediates for the synthesis of manifold chemicals. It is clear that for cyclic carbonates to serve as commodity chemicals, inexpensive, efficient, and recoverable catalytic systems that are active under mild conditions of temperature and pressure are required …”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that compound 3 is the product of two distinct reactions (see Scheme 4). One is the insertion of a single unit of benzaldehyde into the γ‐carbon position of the NacNac ligand, analogous to the insertion of other small unsaturated molecules at this position seen previously by the Mulvey group and other groups involving, for example, alkenes, alkynes, isocyanates, isothiocyanates, carbodiimides, CO 2 or diphenylketene [4–54] . The second is the initiation of a Tishchenko reaction, which describes the dimerization of aldehydes to the corresponding carboxylic ester, in this case two units of benzaldehyde converting to benzyl benzoate.…”
Section: Resultsmentioning
confidence: 89%
“…As beautifully highlighted by Williard in 1993, the range of intermediate structures which may be obtained from similarly long established organolithium reactions is significant, presenting a far more complex picture of organolithium reactions than is typically given in organic textbooks [20] . Exciting steps forward have been trodden in the development of new mechanistic insights and enhanced stability of commonly used organometallic reagents by the Capriati , Garcia‐Alvarez and Hevia groups, primarily in the deployment of such reagents in air, potentially revolutionising the safety and accessibility of such reactions [21–29] . These ongoing developments clearly show that we have not yet had the final word on the mechanisms, structures and behaviours of organolithium and organomagnesium reagents, and that this field remains a thriving and heavily utilised area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Going one step further, and bearing in mind the following phrase (coined by P. T. Anastas and J. C. Warner, usually considered the fathers of the Green Chemistry concept): “The best solvent is no solvent” , [6] Feringa and coworkers firstly described the possibility to promote a more sustainable, faster and scalable direct Pd‐catalyzed coupling of organolithium compounds without the need of any external/additional organic solvents [7] . In this vein, and following this “solventless ” idea, we have successfully extended this s ‐block‐based sustainable methodology to the addition of RLi/RMgX reagents into cyclic carbonates [8] …”
Section: Introductionmentioning
confidence: 99%
“…[7] In this vein, and following this "solventless" idea, we have successfully extended this s-block-based sustainable methodology to the addition of RLi/RMgX reagents into cyclic carbonates. [8] Aside from the Green Chemistry point of view, the previous studies on the use of polar organometallic compounds in the aforementioned unconventional and biorenewable reaction media (water, glycerol or DESs) also revealed that, in some cases, unique chemoselectivities and enhanced performances can be accomplished under these non-Schlenk-type conditions. [4,5] In this sense, Capriati and co-workers recently reported the sequential double addition of highly-polar reagents (RLi/RMgX) to nitriles which, in contrast to classical methods (that require inert atmospheres, dried organic solvents and low temperatures), proceeds quickly, efficiently and chemoselectively at room temperature, under air and using water as the only reaction media, thus giving rise to the desired tertiary carbinamines in yields up to 98 % (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%